Valores em jogo : cerimônias esportivas como rituais seculares de emulação de valores - Medeiros, Ana Gabriela Alves (2012)
The current study is aimed to elaborate an analysis on the emulation of values through rituals in a specific context: sports. To this end, we start from the comprehension that sport ceremonies such as the Olympic ceremonials embrace a ritualistic dimension which figures as a privileged stage to celebrate values (MORÁGAS, MacALOON and LLINÉS; 1995). The Olympic Games as central reference to other competitions is evident in the sport field in such a way that the quantity of olympics is increasing embracing sport competitions from the community level until the world context. It is noticeable that these competitions, directly or indirectly, are based on the Olympic model (as they have a symbolic flame , parade of delegations, oaths, hymns, among other elements). Based on this hypothesis, we tried to identify and analyze the values which orient different school games as well as the meanings and senses attributed to the opening ceremonies and sport by students-athletes and organizers who took part on four different school games. To do so, we combined the data that came from direct observation of the ceremonies, guided interviews with athletes and organizers, as well as questionnaires. Based on the previous hypothesis, it was noticeable that these school Olympics emulated the Olympic ceremony and its values and at the same time the promoted their own identity and specific values. However, through the organizer s speeches, the specific values of the events they promoted were difficult to distinguish from the Olympics and/or the values associated to sports in general. It was also perceptible that as more local the school games were (with smaller size and population), the shape of the ceremonies were featured in a more flexible way, specially, in regards to how and in which order the protocol elements were presented during the ceremony. In regards to the valuing representations of Olympic elements and symbols, it is clear that the ritual aspect of the sport ceremonies are objectively slightly comprehended on their meanings, but, we are subsidized to argue that the ceremony seems to keep its social efficacy in the production of beliefs